3D printed templates improve the accuracy and safety of pedicle screw placement in the treatment of pediatric congenital scoliosis - Jun Cao (BMC, 2021)
Abstract Background Three-dimensional (3-D) printed guidance templates are being increasingly used in spine surgery. The purpose of this study was to determine if 3D printed navigation templates can improve the accuracy of pedicle screw placement and decrease the complication rate compared to freehand screw placement in the treatment of children with congenital scoliosis. Methods The records of pediatric patients with congenital scoliosis treated at our hospital from January 2017 to January 2019 were retrospectively reviewed. Patients were divided into those where a 3D printed guidance templated was used and those in which the freehand method was used for pedicle screw placement. The accuracy rate of pedicle screw placement, surgical outcomes, and complications were compared between groups. Results A total of 67 children with congenital scoliosis were included (43 males and 24 females; mean age of 4.13 ± 2.66 years; range, 2–15 years). There were 34 children in the template-assisted group and 33 in the freehand group. The excellent accuracy rate of pedicle screw placement was significantly higher in the template-assisted group (96.10% vs. 88.64%, P = 0.007). The main Cobb angle and kyphosis angle were similar between the 2 groups preoperatively and postoperatively (all, P > 0.05), and in both groups both angles were significantly decreased after surgery as compared to the preoperative values (all, P < 0.001). The degree of change of the Cobb angle of the main curve and kyphosis angle were not significantly different between the 2 groups. There were no postoperative complications in the template group and 4 in the freehand group (0% vs. 12.12%; P = 0.009). All 4 patients with complications required revision surgery.